2017
DOI: 10.1155/2017/1852897
|View full text |Cite
|
Sign up to set email alerts
|

Network Entropy and Systemic Risk in Dynamic Banking Systems

Abstract: We investigate network entropy of dynamic banking systems, where interbank networks analyzed include random networks, smallworld networks, and scale-free networks. We find that network entropy is positively correlated with the effect of systemic risk in the three kinds of interbank networks and that network entropy in the small-world network is the largest, followed by those in the random network and the scale-free network.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…We first investigate whether this kind of entropy is effective to detect the network structural variance in time series. [9,10]. Each financial crisis indicates the significant variance in entropy associated with dramatic network structural changes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We first investigate whether this kind of entropy is effective to detect the network structural variance in time series. [9,10]. Each financial crisis indicates the significant variance in entropy associated with dramatic network structural changes.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, an investigation of the thermodynamic properties has been performed by physicists by using the perspective and theoretical results of the network theory [5,7,10]. Network entropy has been extensively used to characterise the salient features of the structure in the network dynamics [9]. For example, the von Neumann entropy can be used as an effective characterisation of network structure, commencing from a quantum analogue in which the Laplacian matrix plays the role of the density matrix [11,12].…”
Section: Related Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Besides, Barucca et al [20] made extended clearing models of interdependent liabilities by considering the uncertainty of banks' external assets, and presented a comprehensive modeling framework for systemic risk in the interbank market. He and Li [21] investigated the systemic risk in the interbank market with different network topologies. They found that network entropy was positively correlated with the effect of systemic risk in the three types of interbank networks.…”
Section: Introductionmentioning
confidence: 99%